Learning through a separation process - Trine Ørbæk (Nordic Journal of Art and Research)
In this article, I present an embodied a/r/tographical inquiry of my bodily and emotional responses experienced while going through a separation process, and a description of what I learned as part of this process that has implications for how I intend to teach and develop student teachers’ relational competence. By invoking the context of emergence, currere, the in-between and living inquiry, and in dialogue with the concepts of embodied affectivity and embodied interaffectivity, I observe the unfolding of themes such as activation of bodily resonance, the sharing of embodied experiences and embodied meaning-making, coming together to reveal an insight into relational competence as an embodied phenomenon. I have also revealed an awareness of my bodily inquiry and the merging of moving and writing. The implications of this study for teacher education may well include encouraging student teachers to consider their own relational competence by nurturing and enriching their own bodily awareness of a capacity to engage in meaningful and compassionate ways both with themselves and their pupils, not least when faced with unexpected and provocative situations in their practicum. Applying embodied a/r/tography as a method for developing student teachers’ relational competence may offer opportunities for including student teachers’ wonderings, feelings, reflections and meta-reflections as a means of knowing on their path to becoming teachers.